2021
DOI: 10.3390/ijerph18042093
|View full text |Cite
|
Sign up to set email alerts
|

Family Physicians’ Standpoint and Mental Health Assessment in the Light of COVID-19 Pandemic—A Nationwide Survey Study

Abstract: During the coronavirus disease 2019 (COVID-19) outbreak, family physicians (FPs) are the backbone of the healthcare system with considerable impact on the general population, and their well-being is of great importance. The aim of this investigation was to assess FPs mental health, as well as knowledge, attitudes and practices (KAPs) regarding the pandemic, and opinions on non-communicable disease (NCD) health care provided to patients. A cross-sectional study was carried out with a sample of 613 FPs. Anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 48 publications
6
20
0
2
Order By: Relevance
“…Our research revealed different effects on men and women GPs and different use of support services. This is consistent with international literature which reports gender differences in stress, burnout, anxiety and depression 9,21,22,[24][25][26][27] and greater job strain amongst women in dual-doctor marriages during the pandemic. 28 These differences may arise as a result of gendered social norms around willingness to disclose difficulties, or due to socially constructed gender roles in the home that proliferated during COVID-19 lockdowns, negatively impacting women in employment.…”
Section: Comparison With Existing Literaturesupporting
confidence: 91%
See 1 more Smart Citation
“…Our research revealed different effects on men and women GPs and different use of support services. This is consistent with international literature which reports gender differences in stress, burnout, anxiety and depression 9,21,22,[24][25][26][27] and greater job strain amongst women in dual-doctor marriages during the pandemic. 28 These differences may arise as a result of gendered social norms around willingness to disclose difficulties, or due to socially constructed gender roles in the home that proliferated during COVID-19 lockdowns, negatively impacting women in employment.…”
Section: Comparison With Existing Literaturesupporting
confidence: 91%
“…GP partners may also require targeted support as they described greater pressures associated with management workload due to changes to service delivery, staff shortages and vaccination rollout, which supports other recent studies showing an association between older age and higher stress in GPs. 25,31,32 Further research may be needed to explore recently qualified and trainee GPs' experiences as our findings suggest they have faced differing challenges that may affect longer-term retention and wellbeing.…”
Section: Comparison With Existing Literaturementioning
confidence: 98%
“…Studies measuring stress placed GPs, on average, into 'borderline' or 'stressed' categories of the perceived stress scale (PSS) 30,[36][37][38][39] and, using other stress scales, moderate to severe stress was reported in between 9.5% of GPs in Oman 40 and 24.7% of GPs in Portugal. 41 In terms of burnout, studies found the greatest difficulties related to emotional exhaustion, with 24.5% to 46.1% of GPs reporting high burnout symptoms relating to the emotional exhaustion components of the scale.…”
Section: Psychological Wellbeingmentioning
confidence: 99%
“…46 Posttraumatic stress symptoms (PTSS) were reported in 10.6% of GPs in France, 36 moderate to severe symptoms were reported in 45.2% of GPs in Croatia 36 and 32% of GPs in Italy presented with significant PTSS. 46 Occupational groups Among four studies of mixed groups of healthcare workers (HCWs), primary care doctors reported higher levels of personal perceived stress, 37,38 worse burnout scores (relating to lower 'compassion satisfaction' and higher 'compassion fatigue'), 38 worse depression scores, 39 greater reporting of PTSS 32 and lower job satisfaction than other specialty groups. 29…”
Section: Psychological Wellbeingmentioning
confidence: 99%
“…Researchers have instead examined local or regional PHC levels of preparedness or response to the pandemic 5 , 6 , 7 or studied patient activity in PHC, noting decreases in the provision of chronic care [8] and screening [9] , and declines in the number of physical consultations in both practice [ 10 , 11 ] and pharmacies [12] . Publications of surveys of PHC providers have attempted to highlight their levels and causes of anxiety [ 13 , 14 ]. Additionally, a few multi-country papers, policy briefs and guidance have described key service changes, innovations across Europe, and the impacts on patients with chronic conditions 15 , 16 , 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%